BAHASA DAN GENDER DALAM PEMAKAIAN BAHASA KANAK-KANAK DI KOTA PADANG (Language and Gender in the Language Use of Children in Padang) - Wahyudi, Wahyudi (Balai Bahasa Sumatra Barat, 2016)
So far, study on language and gender usually focuses on adults. The fact that the study doesnot cover adolescents yet underlies this study. This descriptive-qualitative writing aims at describingthe linguistic and nonlinguistic aspect of children language in use from both linguistic and gender perspective. The data were taken from kindergarten students in Padang who belong to middle-low level. The data were collected through observation, questionnaire, and speech recording. Then, the data were analyzed by using distribution method with mark readingtechnique and matching method with pragmatic technique. This research found that use of children’s language has differences between the male and female students, although it wasnot striking. The language differences can be seen from the diction or choice of word, interjection, and intonation.